(secx-secy)/(tanx+tany)+(tany-tanx)/(secx+secy)
=?
Answers
Answered by
0
Step-by-step explanation:
The simplified value of (secx secy+tanx tany)2−(secx tany tanx secy)2 is
A) -1
B) 0
C) sec2x
D) 1
Correct Answer:
D) 1
Description for Correct answer:
(sec x.sec y+tan x.tan y)2−(sec x.tan y+tan x.sec y)2
=(sec2x.sec2y+tan2x.tan2y+2sec x.sec y.tan x.tan y)
−(sec2x.tan2+tan2x.sec2y+2secx.secy.tanx.tany)
=sec2x.sec2y+tan2x.tan2y−sec2x.tan2y−tan2x.sec2y
=sec2x.sec2y−sec2x.tan2y
−tan2x.sec2y+tan2x.tan2y
=sec2x(sec2y−tan2y)
−tan2x(sec2y−tan2y)
=sec2x−tan2x=1
Similar questions
English,
2 months ago
English,
2 months ago
Geography,
2 months ago
Social Sciences,
4 months ago
Computer Science,
4 months ago
Physics,
11 months ago
Math,
11 months ago